Konstruksi Argumentasi Hakim dalam Penetapan Wali Hakim pada Perkara Wali Adhal - Nabilah Nabilah (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
The role of the marriage guardian in Islamic law serves as a protective measure for the prospective bride; however, in practice, it is not uncommon for the blood-related guardian to refuse to marry off the woman without a justification recognized under either Sharia or positive law. This situation is known as wali adhal and serves as the basis for the Religious Court to appoint a judicial guardian. This study aims to analyze the forms of wali adhal, examine the judges’ reasoning in using wali adhal as justification for appointing a judicial guardian, and assess its alignment with the principles of Islamic family law and Indonesian positive law through an analysis of the Cirebon Religious Court Decision No. 45/Pdt.P/2022/PA.CN. This study is a normative legal study employing a statutory approach, a case-based approach, and a conceptual approach. Legal materials were analyzed qualitatively through a literature review of legislation, court decisions, legal doctrine, and legal literature. The results of the study indicate that the wali adhal is not only positioned as a legal fact but is also constructed as the basis for legal justification for the transfer of guardianship authority to the judge-guardian. The judge’s reasoning is built through a systematic relationship between the facts of the trial, legal provisions, and the principle of protecting women’s rights. These considerations are consistent with both Indonesian positive law and the principles of Islamic family law, which prioritize public interest, justice, and the protection of women’s rights as the primary objectives of marriage.